Detection and signal processing in the acoustic echolocation system for the blind - R. SALAMON; R. KOWALIK; I. POSTAWKA (Archives of Acoustics)
The paper presents a method of design, the general features and parameters of the acoustic, multibeam echolocation system for the blind which uses an electret microphone array and a digital beamformer with second order sampling. The system in question detects various obstacles that a blind person encounters on his or her way. It also determines the location of obstacles and the presumable shape and gives verbal messages about the situation observed. The paper includes a detailed description of signal processing in the beamformer and the conditions of detecting the observed obstacles. Theoretical and measured beam patterns of the system have been presented as well as the results of detecting and locating obstacles.